Corporate governance ratings on listed companies: An institutional perspective in Latin America - Guadalupe del Carmen Briano-Turrent; Lázaro Rodríguez-Ariza (European Journal of Management and Business Economics (EJM&BE), 2016)
The aim of this paper is to analyse whether institutional factors determine the level of corporate governance compliance among major listed companies in emerging markets of Latin America, a region characterized by a poor legal system, highly concentrated ownership structures, and capital markets relatively less developed. The paper used an unbalanced panel data consisting of 826 observations of the highest ranked companies on the stock exchange indices of Argentina, Brazil, Chile and Mexico during the period 2004-2010. The results provide strong empirical evidence that board independence, ownership concentration and stakeholder orientation affect positively corporate governance ratings, while board size decreases corporate governance compliance in Latin American countries. The study fills a gap in the Latin American literature, providing useful information for determining policies on corporate governance and, in general, for managers and investors of listed companies in Latin America.
Keywords: G34; 650; Institutional theory; Corporate governance; Emerging markets; Latin America; Ratings